Palladium based membranes and membrane reactors for hydrogen production and purification: An overview of research activities at Tecnalia and TU/e. (11th May 2017) - Fernandez, E.; Helmi, A.; Medrano, J.A.; Coenen, K.; Arratibel, A.; Melendez, J.; de Nooijer, N.C.A.; Spallina, V.; Viviente, J.L.; Zuñiga, J.; van Sint Annaland, M.; Pacheco Tanaka, D.A.; et al.
Abstract: In this paper, the main achievements of several European research projects on Pd based membranes and Pd membrane reactors for hydrogen production are reported. Pd-based membranes have received an increasing interest for separation and purification of hydrogen. In addition, the integration of such membranes in membrane reactors has been widely studied for enhancing the efficiency of several dehydrogenation reactions. The integration of reaction and separation in one multifunctional reactor allows obtaining higher conversion degrees, smaller reactor volumes and higher efficiencies compared with conventional systems. In the last decade, much thinner dense Pd-based membranes have been produced that can be used in membrane reactors. However, the thinner the membranes the higher the flux and the higher the effect of concentration polarization in packed bed membrane reactors. A reactor concept that can circumvent (or at least strongly reduce) concentration polarization is the fluidized bed membrane reactor configuration, which improves the heat transfer as well. Tecnalia and TU/e are involved in several European projects that are related to development of fluidized bed membrane reactors for hydrogen production using thin Pd-based (<5 μm) supported membranes for different application: InDEMCAMER project a water gas shift (WGS) membrane reactor was developed for high purity hydrogen production.ReforCELL aims at developing a high efficient heat and power micro-cogeneration system (m-CHP) using a methane reforming fluidized membrane reactor. The main objective ofFERRET is the development of a flexible natural gas membrane reformer directly linked to the fuel processor of the micro-CHP system.FluidCELL aims the Proof-of-Concept of a m-CHP system for decentralized off-grid using a bioethanol reforming membrane reactor.BIONICO aims at applying membrane reactors for biogas conversion to hydrogen. The fluidized bed system allows operating at a virtually uniform temperature which is beneficial in terms of both membrane stability and durability and for the reaction selectivity and yield. Highlights: Scale-up of thin Pd-based membrane manufacturing. Long-term stability of thin Pd-based supported membranes. Performance of fluidized bed membrane reactors including thin Pd-based supported membranes.